RNF216 is essential for spermatogenesis and male fertility. Issue 5 (15th January 2019) - Melnick, Ashley F; Gao, Yuen; Liu, Jiali; Ding, Deqiang; Predom, Alicia; Kelly, Catherine; Hess, Rex A; Chen, Chen
Abstract: Ring finger protein 216 (RNF216) belongs to the RING family of E3 ubiquitin ligases that are involved in cellular protein degradation. Mutations in human Rnf216 gene have been identified in Gordon Holmes syndrome, which is defined by ataxia, dementia, and hypogonadotropism. However, the gene function of Rnf216 in mammalian species remains unknown. Here, we show that targeted deletion of Rnf216 in mice results in disruption in spermatogenesis and male infertility. RNF216 is not required for female fertility. These findings reveal an essential function of RNF216 in spermatogenesis and male fertility and suggest a critical role for RNF216 in human gonadal development.